Unexpected Candidal Hyphae in Oral Mucosa Lesions-A Clinico-Pathological Study - Jeremy Edel; Osnat Grinstein-Koren; Orit Winocur-Arias; Ilana Kaplan; Anna Schnaiderman-Shapiro; Amos Buchner; Marilena Vered; Ayelet Zlotogorski-Hurvitz (MDPI AG, 2022)
Background: Oral mucosal biopsies might harbor candidal hyphae (CH) in the absence of any clinical signs or symptoms. Aim: To assess oral mucosa biopsies for the frequency of unexpected CH and characterize their clinico-pathological features. Materials and Methods: All biopsy reports (2004-2019) were searched using CH/candida/candidiasis as key words. Cases with clinical diagnosis of oral candidiasis (OC) were excluded. Demographic data, health status, smoking habits, clinical features and diagnoses were collected. Statistical analysis included the chi-square test; significance was set at p < 0.05. Results: Of all the biopsies, 100 (1.05%) reported microscopical evidence of CH without typical clinical signs/symptoms of OC. Fifteen cases were from healthy, non-smoking patients. CH was common on buccal mucosa (38%) and lateral tongue (23%). The tip of tongue (OR = 54.5, 95% CI 9.02-329.4, p < 0.001) and lateral tongue (OR = 3.83, 95% CI 2.4-6.09, p < 0.001) were more likely to harbor CH-positive lesions. CH-positive lesions were diagnosed as epithelial hyperplasia (55%) and exophytic reactive lesions (30%). No correlation was found between CH and the grade of epithelial dysplasia. Conclusions: Microscopic evidence of CH embedded into oral epithelium without typical signs/symptoms of OC is rare, especially in healthy, non-smokers. Since CH was occasionally found in oral sites prone to local trauma and in association with reactive lesions, in absence of host co-morbidities, the contribution of local mechanical forces to CH embedment cannot be ruled out.